2023
DOI: 10.2298/pan200309011t
|View full text |Cite
|
Sign up to set email alerts
|

Testing the efficiency of emerging markets: Evidence from nonlinear panel unit tests

Abstract: In this study, we investigate market efficiency considering nonlinearities by testing the weak-form market efficiency of the stock markets of Brazil, China, Russia, Turkey, and South Africa using recently proposed nonlinear panel unit root tests. The stock markets of these emerging countries are deliberately selected for their market capitalization to form a homogenous panel. The results of nonlinear models indicate that the stock market indexes are stationary and weak-form inefficient. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…This test examines a dataset across a spectrum of embedding dimensions, ranging from two to six, offering a nuanced analysis of the data's stochastic nature. The BDS test stands out among alternative methodologies for its ability to enhance analytical rigor, as noted by Turguttopbaş and Omay [160] and Hasanov et al [161]. Its principal advantages include the mitigation of model misspecification errors and the reduction of biases stemming from subjective judgment.…”
Section: Modelmentioning
confidence: 99%
“…This test examines a dataset across a spectrum of embedding dimensions, ranging from two to six, offering a nuanced analysis of the data's stochastic nature. The BDS test stands out among alternative methodologies for its ability to enhance analytical rigor, as noted by Turguttopbaş and Omay [160] and Hasanov et al [161]. Its principal advantages include the mitigation of model misspecification errors and the reduction of biases stemming from subjective judgment.…”
Section: Modelmentioning
confidence: 99%
“…Additionally, investors in developing countries often have to contend with unreliable information and high volatility at multiple political, economic, and social levels (Alkhatib & Harasheh, 2014). Several studies confirm the inefficiency of emerging markets (Nguyen & Parsons, 2021;Sadat & Hasan, 2019;Turguttopbas, 2021). Emerging markets lack full integration with world capital markets, and investors could earn arbitrage profits from market inefficiency in these countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The market efficiency at the weak level of Brazil, China, Russia, Turkey, and South Africa stock markets was subject to testing. Turguttopbas (2021) uses nonlinear statistical methods to test market efficiency at a weak level for these markets and found that the stock market indices in these countries are stationary and inefficient at weak levels. Furthermore, Dias et al (2020) (Miloş et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%